Relevansi Nilai Pendidikan Islam dan Tasawuf dalam Suluk Bismillah bagi Abdi Dalem Padepokan Jabalahad Keraton Surakarta - Ririn Perdananingrum; A. Dardiri Hasyim (Program Pascasarjana UNU Surakarta, 2022)
This study aims to find out: 1) Islamic Education Values in Suluk Bismillah for Abdi Dalem in Padepokan Jabalahad Keraton Surakarta Hadiningrat, 2) Sufism Teachings in Suluk Bismillah for Abdi Dalem in Padepokan Jabalahad Keraton Surakarta Hadiningrat, 3) Relevance of Islamic Education Values and Sufism Teachings in Suluk Bismillah for Abdi Dalem in Padepokan Jabalahad Keraton Surakarta Hadiningrat. This research is library research, namely collecting research data from the literature and making the